Identificación de discriminación sexual e identidad de género en medios de comunicación radial de la ciudad de Loja y Catamayo, durante el periodo académico octubre 2016- febrero 2017 - Tacuri Chinchay, Jose Luis (2018)
The radio from its origin has become a mass medium of communication that reaches almost all people, despite the emergence of new technologies this has not managed to be displaced. Focusing on the radio as a portable communication resource and easy accessibility for today's society that lives vertiginously and it is almost impossible to sit and watch a screen with tranquility and care. The radio was born with a single purpose, to improve the communication of society. Colombia was the pioneer in giving good use to this communicative instrument, by the hand of Monsignor José Joaquín Salcedo Guarín, who was the creator of the radio schools and with it in 1947 the first popular radio (SUTATENZA) was born, Nowadays it is "confused in an extraordinary way with the concept of popular radio, which was created to educate marginal sectors" (Geerts, Oeyen & Villamayor, 2004, p.33). The type of stations that exist today, most are commercial, has lost the educational focus because its owners think it is not profitable. How do you know that it is not profitable? If they have not tried it, what has given way to musical programs without a constructive approach; in many cases, empty. In some stations these spaces of radio fun direct their planning to generate humor using vulnerable groups such as: LGBTI, MAJOR ADULT, PEOPLE WITH ALCOHOLISM PROBLEMS, among others, to achieve a higher rating, the one that most stands out Radio Boquerón with its "Afternoon Fun" program, the same one that is broadcasted in the evening hours "13:00 a.m. to 6:00 p.m. hours "from Monday to Friday. López Vigil (2005) in his passionate radio shows that we must be responsible with communication, because "the radio makes us visible tells us before thousands of people." Society believes in what is said in the microphones, so it is important to be committed to the communicative work that is carried out. If the communicative activity is carried out with vocation, the expectation of having a more inclusive society will no longer be just a figment.